2017
DOI: 10.1177/0033354917723601
|View full text |Cite
|
Sign up to set email alerts
|

Systems Thinking and Simulation Modeling to Inform Childhood Obesity Policy and Practice

Abstract: Systems thinking, especially with simulation models, facilitates understanding of complex health policy problems. Using a simulation model to educate legislators, educators, and health experts about the policies that have the greatest short- and long-term impact should encourage strategic investment in low-cost, high-return policies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…However, our review suggested that the desired level of comprehensive, in‐depth, interdisciplinary modelling practice has not really occurred yet. Except for a few studies that explicitly described the interdisciplinary expertise involved in the modelling , the synergistic effects of interdisciplinary collaboration have not generated new insights and significant progress in obesity research. This dearth exposes the challenge posed by a lack of well‐trained interdisciplinary researchers with diverse backgrounds, which will continue to pose major obstacles to applying SM approaches in public health research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our review suggested that the desired level of comprehensive, in‐depth, interdisciplinary modelling practice has not really occurred yet. Except for a few studies that explicitly described the interdisciplinary expertise involved in the modelling , the synergistic effects of interdisciplinary collaboration have not generated new insights and significant progress in obesity research. This dearth exposes the challenge posed by a lack of well‐trained interdisciplinary researchers with diverse backgrounds, which will continue to pose major obstacles to applying SM approaches in public health research.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the model developed by Homer and colleagues in 2006, a team comprising state legislators, legislative staff members and experts in nutrition, PA, epidemiology, economics and systems dynamics developed a system dynamics model to predict obesity among children in Georgia, and the team updated the model in 2014 . The updated model simulations suggested that, compared with a scenario with no policy change in which the prevalence of obesity among children in Georgia would remain 18% from 2014 to 2034, mandating daily school physical education (PE) would reduce the prevalence of obesity in childhood to 12%, integrating moderate to vigorous PA into elementary classrooms would reduce the prevalence to 10%, and if all policies were implemented simultaneously, the prevalence would be reduced to 3%.…”
Section: Applications Of Systems Modelling In Obesity Researchmentioning
confidence: 99%
“…Many diseases and conditions, such as type 2 diabetes mellitus, coronary heart disease, cancer, hypertension, and musculoskeletal disorders, are associated with obesity [ 46 ]. The included papers investigate obesity among children [ 47 , 48 , 49 , 50 ], women of reproductive age [ 51 ], individuals in low-income urban areas [ 52 ], and lower-socioeconomic status (SES) groups [ 53 , 54 ]. The objectives of the selected papers can be categorized into two main groups: (a) reducing obesity (reactive responses) and (b) presenting interventions for obesity prevention (proactive responses).…”
Section: Discussionmentioning
confidence: 99%
“…Allender and associates [ 56 ] discussed the causes of obesity in four domains: fast food and junk food, social influences, physical activity, and participation in sports. Although a study places more emphasis on building outdoor activity spaces for children [ 48 ], it was also reported that physical education is more effective than physical activity in reducing obesity among children [ 49 ]. Interestingly, Chen and associates [ 54 ] concluded that enhancing an individuals’ status from lower- to middle-income levels would be effective in controlling obesity and being overweight.…”
Section: Discussionmentioning
confidence: 99%
“…Approaches to systems modelling include 'systems dynamics modelling' and 'agent-based modelling', and although in the early stages, has been applied in a range of applications including the impact of physical activity and diet on weight gain/loss (Abdel-Hamid, 2003), policy effects of allocating revenue collected by SSB taxation (Liu, Osgood, Gao, Xue, & Wang, 2016), the impact of policy interventions on the prevalence of childhood obesity (Powell et al, 2017), and comparing obesity interventions using network-based targeting methods with interventions (Beheshti, Jalalpour, & Glass, 2017), among others. The use of systems modelling in obesity research is a growing area that provides a platform to model interactions between agents in a simulated world, proving invaluable in testing interventions and the effects of policy (Lal et al, 2017;Shoham, Hammond, Rahmandad, Wang, & Hovmand, 2015;Xue et al, 2018).…”
Section: Research Question 1: Where Are the Views Of Stakeholders Conmentioning
confidence: 99%